In vivo anti-tumor effects of citral on 4T1 breast cancer cells via induction of apoptosis and downregulation of aldehyde dehydrogenase activity - Nigjeh, Siyamak Ebrahimi; Yeap, Swee Keong; Nordin, Norshariza; Rahman, Heshu; Rosli, Rozita (MDPI, 2019)
Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer death among females globally. The tumorigenic activities of cancer cells such as aldehyde dehydrogenase (ALDH) activity and differentiation have contributed to relapse and eventual mortality in breast cancer. Thus, current drug discovery research is focused on targeting breast cancer cells with ALDH activity and their capacity to form secondary tumors. Citral (3,7-dimethyl-2,6-octadienal), from lemon grass (Cymbopogon citrates), has been previously reported to have a cytotoxic effect on breast cancer cells. Hence, this study was conducted to evaluate the in vivo effect of citral in targeting ALDH activity of breast cancer cells. BALB/c mice were challenged with 4T1 breast cancer cells followed by daily oral feeding of 50 mg/kg citral or distilled water for two weeks. The population of ALDH+ tumor cells and their capacity to form secondary tumors in both untreated and citral treated 4T1 challenged mice were assessed by Aldefluor assay and tumor growth upon cell reimplantation in normal mice, respectively. Citral treatment reduced the size and number of cells with ALDH+ activity of the tumors in 4T1-challenged BALB/c mice. Moreover, citral-treated mice were also observed with smaller tumor size and delayed tumorigenicity after reimplantation of the primary tumor cells into normal mice. These findings support the antitumor effect of citral in targeting ALDH+ cells and tumor recurrence in breast cancer cells.